PERBANDINGAN KINERJA BANK PEMERINTAH DAN BANK SWASTA DENGAN RASIO CAMEL SERTA PENGARUHNYA TERHADAP HARGA SAHAM - Etty M. Nasser (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
The objective of this research is to identify whether there is a significant difference between performance of state owned bank s and private banks. The mea-sure of performance is based on financial ratios CAMEL, which consist of CAR as represent of Capital, RORA as represent of asset quality, NPM as represent of Management, ROA as represent of earnings and LDR as represent of liquidity. This research also identify the influence of CAMEL to stock price.The sample of 26 state owned banks and 22 private banks. Kolmogorov Smimov test is used to test the normality of data distribution. For normally distributed data consist of CAR, NPM and LDR, test are conductable using West as parametric test. Meanwhile, RORA and ROA which non normally distributed, test are conducted using Mann-Whitney, as non parametric test to compare the difference between state owned banks and private bank's performance. The multiple reg4ession model is used to determine the relationship between CAMEL and stock price.The empirical result of this research indicates that the CAR, RORA, ROA dan LDR of state-owned banks and the private banks have a similar perfonance. Inspite of this, there is no significant difference in NPM between the state-owned banks and the private banks. The other analysis that CAMEL have simultaneously significant influence to the stock price.Keywords: CAMEL, financial ratio, bank performance, stock prise